2021
DOI: 10.1111/jerd.12839
|View full text |Cite
|
Sign up to set email alerts
|

Effect of assessor's sex on visual color matching in dentistry: A systematic review of the literature

Abstract: Objectives: To evaluate systematically the influence of sex of dental professionals on their capability for visual color matching. Materials and Methods:The protocol was registered on PROSPERO (CRD42020205393). PICOS question was develop based on the population, intervention, comparison, outcomes, and study design (PICOS). Eligibility criteria included cross section studies, randomized clinical trials and cohort studies that compared the effect of sex on the visual color matching process. Five electronic datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…On this basis, a separate line of chromatic training could be developed, which should be considered to ensure that dentistry professionals receive training in subjective selection of gingival colour, thereby improving results. According to a recent systematic review [31] on the controversial topic of the role of gender in dental colour selection, the lack of methodological homogeneity may explain the discrepancies in the results obtained.…”
Section: Subjective Versus Objective Metodologymentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, a separate line of chromatic training could be developed, which should be considered to ensure that dentistry professionals receive training in subjective selection of gingival colour, thereby improving results. According to a recent systematic review [31] on the controversial topic of the role of gender in dental colour selection, the lack of methodological homogeneity may explain the discrepancies in the results obtained.…”
Section: Subjective Versus Objective Metodologymentioning
confidence: 99%
“…There is no consensus in prior studies about whether there is any difference in the subjective perception of the dental colour space by men and women. Some have concluded that men and women perceive dental colour in a similar manner [11,[26][27][28][29][30][31][32], while other articles [11,[33][34][35][36] have identified statistically significant differences in favour of women's identification of colour.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals' satisfaction with their teeth appearance is a fundamental aspect of human social interactions, resulting in improved psychological well-being and a better quality of life (1,2) . The accelerating pursuit of an esthetic smile in modern societies has increased the expectations and demands for esthetic tooth-colored restorations (3)(4)(5) . Dental resin composites are becoming the restorative materials of choice for most anterior and posterior restorations in daily practice (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%
“…The assessor's age, gender, anxiety, mood, and drugs/medications can also influence color perception (15,31) . In contrast, instrumental methods (e.g., spectrophotometers, colorimeters) are objective, more accurate, and more consistent (5). No gold standard color measurement tool exists.…”
Section: Introductionmentioning
confidence: 99%